Attribution Retraining Group Counseling Technique to Reduce Student’s Learned Helplessness Behavior (Universitas Negeri Semarang, 2018)
This study aimed to determine the impact of attribution retraining group counseling technique on student’s learned helplessness. One-group pretest-posttest design was used in this study involving a total of 5 students as participants. The results of paired t-test showed that the student learned helplessness level can decreased at posttest (39.58%) than at assesment pre test (68.33%; t = 7.14, p < 0.01). Further, this study was focused to discuss the possibility of implementing attribution retraining in overcoming the problem of student’s learned helplessness behavior.